Minimal skin dose increase in longitudinal rotating biplanar linac-MR systems: examination of radiation energy and flattening filter design. (6th April 2016) - Keyvanloo, A; Burke, B; St. Aubin, J; Baillie, D; Wachowicz, K; Warkentin, B; Steciw, S; Fallone, B G
Abstract: The magnetic fields of linac-MR systems modify the path of contaminant electrons in photon beams, which alters patient entrance skin dose. Also, the increased SSD of linac-MR systems reduces the maximum achievable dose rate. To accurately quantify the changes in entrance skin dose, the authors use EGSnrc Monte Carlo calculations that incorporate 3D magnetic field of the Alberta 0.5 T longitudinal linac-MR system. The Varian 600C linac head geometry assembled on the MRI components is used in the BEAMnrc simulations for 6 MV and 10 MV beam models and skin doses are calculated at an average depth of 70 μ m using DOSXYZnrc. 3D modeling shows that magnetic fringe fields decay rapidly and are small at the linac head. SSDs between 100 and 120 cm result in skin-dose increases of between 6%–19% and 1%–9% for the 6 and 10 MV beams, respectively. For 6 MV, skin dose increases from 10.5% to 1.5% for field-size increases of 5 × 5 cm 2 to 20 × 20 cm 2 . For 10 MV, skin dose increases by 6% for a 5 × 5 cm 2 field, and decreases by 1.5% for a 20 × 20 cm 2 field. Furthermore, the proposed reshaped flattening filter increases the dose rate from the current 355 MU min −1 to 529 MU min −1 (6 MV) or 604 MU min −1 (10 MV), while the skin-dose increases by only an additional 2.6% (all percent increases in skin dose are relative to D max ). This study suggests that there is minimal increase in the entrance skin dose and minimal/no decrease in the dose rate of the Alberta longitudinal linac-MR system. The even lower skin dose increase at 10 MV offers further advantages in future designs of linac-MR prototypes.